2013
DOI: 10.1158/1055-9965.epi-13-0363
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Adiponectin and Primary Liver Cancer Risk in Middle-Aged Japanese Adults with Hepatitis Virus Infection: A Nested Case–Control Study

Abstract: Background: Excess body weight is an independent risk factor for primary liver cancer, and the role of adiponectin in the pathogenesis of obesity-related malignancies is a focus of research interest. Few prospective studies have examined the association between circulating adiponectin and liver cancer risk, so we investigated this association in a nested case-control study of a population-based prospective cohort in Japan.Methods: From 18,628 target participants of ages 40 to 69 years who returned the baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…Most of researchers have proven that lower adiponectin is associated with more aggressive clinicopathological features and lower survival rates. However, some studies have reported contradictory results, suggesting that higher serum adiponectin was related to cancer progression and worse prognosis [21, 22]. In our study, patients with metabolic syndrome had lower serum adiponectin concentrations, but we did not find associations with tumor size or clinical stage of disease.…”
Section: Discussioncontrasting
confidence: 88%
“…Most of researchers have proven that lower adiponectin is associated with more aggressive clinicopathological features and lower survival rates. However, some studies have reported contradictory results, suggesting that higher serum adiponectin was related to cancer progression and worse prognosis [21, 22]. In our study, patients with metabolic syndrome had lower serum adiponectin concentrations, but we did not find associations with tumor size or clinical stage of disease.…”
Section: Discussioncontrasting
confidence: 88%
“…Pooling data of 13 studies [ 21 , 24 26 , 28 , 30 33 , 35 37 , 40 ] with 2092 participants were evaluated on the association between AdipoQ levels and HCC risk. Heterogeneity analysis showed significant heterogeneity among the studies (I 2 = 98.2%, P = 0.000), and the random-effect model was applied.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, no association between circulating adiponectin and risk of endometrial cancer, the cancer type that shows that strongest association with obesity, was observed in the Nurses Health Study, but the number of included cases was limited [62]. Interestingly, adiponectin, in particular HMW-adiponectin, has been associated with higher risk of hepatocellular carcinoma in two nested case-control studies of prospective cohorts including EPIC [63,64], but not in another nested case-control study [65].…”
Section: Adiponectinmentioning
confidence: 96%